COLLABORATION OF STAKEHOLDERS IN THE DEVELOPMENT OF MICRO ENTERPRISES FOR SUSTAINABLE FOOD SECURITY IN TELUK BINTUNI REGENCY - Sangadji, Muhd. Nur; Edy, Nur; Rahman, Abdul; Haryanti, Tuti; Latifah, Ayi; Krisnamurti, Reza Mahendra; Maiwa, Arman; Megasari, Desi; P, Karisma Kondo (Universitas Tadulako, 2024)
The establishment of micro-enterprises for Independent Workers (TKM) aimed at enhancing sustainable food security in Teluk Bintuni Regency, West Papua, is a crucial initiative to bolster local food production sustainably. This study investigates the challenges of TKM and the cooperation among stakeholders in the regional employment expansion initiative. Qualitative research was employed, encompassing field observation, interviews with micro-entrepreneurs and stakeholders, and focus group discussions (FGDs) with local populations. The findings indicate that the Independent Workers (TKM) initiative significantly enhances local economic development by empowering micro-enterprises in food production and processing. Challenges faced by TKM, specifically restricted financial access, market entry, corporate governance, and digital marketing, continue to pose substantial barriers. Cooperation among government agencies, commercial firms, academic institutions, and non-governmental organizations is crucial for addressing these challenges. This study underscores the necessity for a unified strategy to enhance TKM development, fostering sustainable food systems and economic resilience. This collaborative methodology seeks to produce insights for attaining the sustainable development goals (SDGs) associated with poverty alleviation and hunger reduction in the region.